Accurate quantification of pulmonary perfusion ratio in children with congenital heart disease using partial volume corrected 4D flow cardiac magnetic resonance - Lagerstrand, Kerstin; Nyström, Anna; Svensson, Pär-Arne; De Lange, Charlotte; Dangardt, Frida (Frontiers in Pediatrics, 2024)
In children with congenital heart disease (CHD), lung scintigraphy is the reference standard for evaluation of pulmonary perfusion. 4D flow CMR offers a non-ionizing alternative. Due to the intrinsic limitation in the spatial resolution, however, 4D flow may display clinically unacceptable differences compared to the reference standard. This case study aims to highlight the importance of correcting for such partial volume errors to accurately evaluate pulmonary perfusion in small pulmonary arteries.Children with CHD, mainly those with transposition of the great arteries or tetralogy-of-Fallot, referred to CMR from 2020 through 2022 at our clinic, were retrospectively reviewed; n= 37. All patients had been examined with a free breathing, motion-corrected 4D flow protocol. Comparison in pulmonary perfusion (PPR: relative flow through right and left pulmonary arteries) with scintigraphy were performed both for 4D flow before and after partial volume correction.Patients with large pulmonary arteries, 76%, displayed small differences in PPR between modalities (<20%), while patients with arteries of only a few pixels, 24%, displayed differences up to 178%, depending on the relative difference in size between the right and left pulmonary artery. Differences were effectively reduced after partial volume correction (<21%).The present report shows that 4D flow is a promising tool to accurately evaluate the pulmonary perfusion in children with CHD, but that partial volume correction is warranted to overcome its limitation in the spatial resolution. Without such correction, lung scintigraphy is still recommended to ensure high diagnostic certainty in children with small pulmonary arteries.